Kidney-gut crosstalk in renal disease (2020)
Introduction The colon has an important role in managing nitrogenous waste products, electrolytes, and mineral balance during kidney diseases. However, colonic microbiota produces uremic toxins, such as indoxyl sulfate and p-cresyl sulfate, in chronic kidney disease (CKD) patients, which due to their proinflammatory properties contribute to CKD progression. Conversely, in acute renal injury patients, intestinal microbiota could reduce inflammation by secreting short-chain fatty acids and inducing a renal protective immune response. However, since the intestines are the most frequently affected organ in advanced sepsis, colonic microbiota can also represent a negative factor for kidney health in this scenario. Conclusion In the present review, the main characteristics of kidney-gut crosstalk are described.